Saberes, fazeres e narrativas culturais indígenas do baixo Tapajós: a vivência musical do coletivo “as karuana” - Maciel, Michel Albuquerque (2023)
Music is usually conceived historically and judged qualitatively from a eurocentric point of view that usually obscures the logic and understanding of the culture in which it is produced and transmitted. In the indigenous reality, such discussion obeys many variables, due to the load of symbolisms, experiences, realities, and as a political process of identity affirmation and demand for rights. The present work seeks to understand the musical experience of the Coletivo as Karuana Mulheres Indígenas e da Floresta, through the knowledge, positionings, production, and narratives originating from its members. The research was developed in the village of Alter do Chão, located 35 km from the Santarém city, in western Pará. In this work, we used ethnomusicology and case studies. To obtain the data, we carried out bibliographic research, interviews and observation. The group, made up of women from the Borari, Kumaruara and Tapajó ethnicities, performs in songs and actions a movement against the historical and continuous processes of attacks against the indigenous peoples and their territories, as well as shows the identity of its components, worldview and relationship with their ancestors, elements in common with other indigenous groups in the region.